Laboratory Screening of Control Agents Against Isolated Fungal Pathogens Causing Postharvest Diseases of Pitaya in Guizhou, China - Li, Yong; Chen, Haijiang; Ma, Lan; An, Youshan; Wang, Hui; Wu, Wenneng (Frontiers in Chemistry, 2022)
Pitaya, or dragon fruit, is a typical tropical fruit with an appealing taste and diverse health benefits to humans. The plantation of pitaya in Guizhou province in China has greatly boosted the income of local farmers and alleviated poverty. However, the frequent occurrence of postharvest diseases has brought large economic loss. To find a solution, we set out to identify the postharvest disease-causing agents of Guizhou pitaya. Several fungi were isolated from diseased pitaya and identified as species based on the ITS1 sequence similarity. Of them, Penicillium spinulosum, Phoma herbarum, Nemania bipapillata, and Aspergillus oryzae were, for the first time, found to cause dragon fruit disease. In consideration of their prevalence in postharvest fruit diseases, Alternaria alternata H8 and Fusarium proliferatum H4 were chosen as representative pathogens for the drug susceptibility test. Among the tested drugs and plant extracts, 430 g/L tebuconazole and 45% prochloraz were found to be the most potent fungicides against H8 and H4, respectively. The research provides insights into the mechanism and control of postharvest diseases of dragon fruits in Guizhou, China, and thus could be of economic and social significance to local farmers and the government.